Analisis Non Performing Loan, Biaya Operasional Pendapatan Operasional, dan Free Cash Flow Terhadap Nilai Perusahaan - Neng Nia Fania; Dicky Jhoansyah; Faizal Mulia (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The research was aimed at determining the influence of Non Performing Loan, operating expenses to operating income, and free cash flow on firm value conducted in the banking sektor listed on the Indonesian Stock Exchange periode 2018-2022. The object of the research were Non Performing Loan (X1), Operating Expenses to Operating Income (X3), free cash flow (X3), and Firm Value (Y). the research used descriptive and associative methods with quantitative approach. The technique of sampling deployed in the research was non probability sampling approach, namely the purposive sampling technique. The techniques of analysing data applied were test of coefficient of multiple correlation and coefficient of determination, multiple linear regression test, partial test (t-test), and simultaneous test (f test). Based on the result of the research show that there is a relationship of  Non Performing Loan, operating expenses to operating income, and free cash flow toward firm value which is aggregated to 0,659, indicating that the relationship of Non Performing Loan, operating expenses to operating income, and free cash flow toward firm value is included to a strong relationship criteria. Moreover, the result of partial test show that Non Performing Loan negative and significant influence toward firm value, operating expenses to operating income negative and significant influence toward firm value, and free cash flow has positive and insignificant influence toward firm value.